LOSS OF A CHANCE: ASPECTS OF THE LEGAL NATURE OF COMPENSATION ARISING FROM CIVIL LIABILITY (REMUNOM, 2023)
This scientific research analyzes civil liability based on the theory of loss of a chance. This category of damage is recognized and adopted by the Brazilian legal system, however, there is currently no consolidated understanding that defines the legal nature of this institute. At the end of this research, it will be possible to better understand how this type of damage has been applied by the Court of Justice of the State of Espírito Santo and what is the majority understanding of the legal nature of this institute. The methodology used to develop this scientific article is bibliographical research, extracting information from physical books, electronic books, scientific articles, monographs, magazines, civil law enunciations and judgments in Brazil on the subject.